Fast multipoint immobilization of lipase through chiral l-proline on a MOF as a chiral bioreactor. Issue 5 (20th January 2021) - Lirio, Stephen; Shih, Yung-Han; So, Pamela Berilyn; Liu, Li-Hao; Yen, Yun-Ting; Furukawa, Shuhei; Liu, Wan-Ling; Huang, Hsi-Ya; Lin, Chia-Her
Abstract : Successful co-immobilization of Pro and PPL on microporous MOF-1, 4-NDC(Al) (PPL-Pro@MOF-1, 4-NDC(Al)) has been demonstrated. Abstract : In this paper, we describe the facile preparation of a chiral catalyst by the combination of the amino acid, l -proline (Pro), and the enzyme, porcine pancreas lipase (PPL), immobilized on a microporous metal–organic framework (PPL-Pro@MOF). The multipoint immobilization of PPL onto the MOF is made possible with the aid of Pro, which also provided a chiral environment for enhanced enantioselectivity. The application of the microporous MOF is pivotal in maintaining the catalytic activity of PPL, wherein it prevented the leaching of Pro during the catalytic reaction, leading to the enhanced activity of PPL. The prepared biocatalyst was applied in asymmetric carbon–carbon bond formation, demonstrating the potential of this simple approach for chemical transformations.